S32. Outcome Guillain–Barré of syndrome in tertiary care centers in Thailand (extended study). (May 2018) - Sukphulloprat, Puchit; Kulkantrakorn, Kongkiat; Thongchuam, Yuwadee; Sitthinamsuwan, Pasiri; Tantirithisak, Pantila; Nudsasarn, Angkana; Tanprawet, Surat
Abstract : Introduction: Guillain–Barré syndrome (GBS), a common acute polyneuropathy, is seen worldwide with significant morbidity and mortality. Regional data of GBS in Thailand are sprase. Therefore the aim of this study is to identify clinical characteristics, electrophysiologic changes, clinical course, treatment, and outcome of GBS in Thailand. Methods: Retrospective study of GBS patients aged 15 years or older, admitted to Thammasat University Hospital, Bangkok Hospital Medical Center, Phramongkutklao Hospital, and Maharaj Nakorn Chiang Mai Hospital between January 1, 2009 and June 30, 2017. Results: Eighty-two patients were found. Demographic characteristics were collected and described as follows; 56% male sex; average age 49 years; Asian 77%, European 9%, and others 10%. Disease subtypes consist of acute inflammatory demyelinating polyneuropathy 69.5%, acute motor axonal neuropathy 14.6%, and others 15.9%. Average GBS disability score at admission was 3.0. Immunotherapy was intravenous immunoglobulin only 91.7%, plasma exchange plus intravenous immunoglobulin 5%, and steroid 3.3%. Average length of stay was 14.8 days; assisted ventilation rate was 22.0%. After the average of 8-month follow-up, average GBS disability score was 1.8, good outcome (score < 3) was 70.6% and no death. Conclusion: Our study suggests that most GBS patients in Thailand are acute inflammatory demyelinating polyradiculoneuropathy (AIDP) subtype and have a good outcome.